The Implementation of Murabahah bil Wakalah Financing in BRI Syariah Unit Genteng Banyuwangi - Jannah, Naila Wardatul (Fakultas Syariah, 2015)
The purpose of this study is to knowing more about implementation of murabahah bil wakalah in in BRI Syariah Unit Genteng Banyuwangi, need to do research subsequently. This empirical research use statue approach and judicially sociological approach. In this research a method of the data which is used is qualitative data analyses. The results of this research show that the implementation of murabahah bil wakalah financing in Bank BRI Syariah Unit Genteng Banyuwangi not accordance with Regulation of Bank Indonesia article 9 point d, No. 7/46/PBI/2005 about â€œAkad Penghimpunan dan Penyelesaian Dana Bagi Bank yang Melaksanakan Kegiatan Usaha Berdasarkan Prinsip Syariahâ€ mentioned that